Serosurvey of SARS-CoV-2 in dogs and cats from Portugal. (March 2022) - Neves, S.; Anjos, S.; Madeira, B.; Craveiro, H.; Esteves, P.; Neves, T.; Vilhena, H.; Anastacio, S.
Abstract : Purpose: Severe acute respiratory syndrome–coronavirus 2 (SARS-CoV-2) causes COVID-19, which was first reported in humans in 2019, in Wuhan, China. This RNA virus has highly efficient transmission. Sporadic cases of infection in pets have been described. Human to animal transmission seems to occur, however, the epidemiologic role of pets remains unclear. This study aimed to screen dogs and cats from the North and Centre regions of Portugal for the exposure to SARS-CoV-2, during the peak of SARS-CoV-2 human infection in Portugal, which occurred between October 2020 and March 2021. Methods & Materials: A cross-sectional study was conducted in dogs and cats presented to veterinary medical centres from Portugal between October 2020 and March 2021, that required blood sampling as part of their diagnostic plan. Only surplus sera or plasma samples were used in this research. Sera or plasma were tested for the presence of specific antibodies anti-SARS-CoV-2 using a commercial ELISA adapted for multi-species detection (ID Screen SARS-CoV-2Double Antigen Multispecies®, IDVet). Laboratory results were expressed in S/P values and samples with an S/P% ≥ 60% were classified as positive. Results: A total of 107 animals were sampled (dogs n=60; cats n=47). The canine population was composed by 25 purebred and 35 crossbreed dogs, with ages ranging from 5 months to 15 years of age. Cats were mainly of the domestic short-hair breed (n=45), with ages ranging between 6 months and 9 years old. The estimated rate of exposure was of 5.0% (95% CI: 1.71-13.7%) in dogs (n=3) and 2.13% (95% CI: 1.18-14.26%) in cats (n=1). A doubtful result (50≥S/P%<60%) was obtained in 6.7% (95% CI: 2.6-15.9%) of dogs (n=4) and in 4.26% (95% CI: 2.6-15.9%) of cats (n=3). Conclusion: To our best knowledge, this is the first serosurvey conducted in pets in Portugal. An exposure to the agent has been evidenced in dogs and in cats. Further studies must clarify the impact of the exposure in animal health and the role of the pets in spreading the virus.